PEMBUATAN AKUN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI PRODUK PADA KELOMPOK WIRAUSAHA PEMUDA BULU BATU - Amelina, Asmilia; Kamariah, Najmi (ADMIT: Jurnal Administrasi Terapan, 2024)
Promotion is a strategy that is implemented to spread information and encourage prospective consumers to buy the products that are being offered. The primary goal of promotion is to disseminate information, which in turn attracts attention and subsequently influences sales. The emergence of social media has transformed it into a powerful promotional tool that is utilized for the dissemination of information. Almost all social media platforms offer product promotional activities that are presented in visually appealing advertisements. However, the primary challenge for MSMEs in operating a business that utilizes digital technology is the absence of additional knowledge regarding digital marketing. Therefore, in order to increase the awareness of the products offered, KWP Bulu Batu requires a social media account as a promotional tool The objective of this study was to create a social media account as a product promotion media at KWP Bulu Batu in order to spread knowledge about its products. This study was conducted at the Bulu Batu Youth Entrepreneurship Group (KWP) in Bulu Batu, Umpungeng Village Soppeng Regency. This study applied a qualitative descriptive approach. In order to accumulate the necessary information, questionnaires, documentation, interviews, and observations were implemented. The result of this study presented in an Instagram account with 12 posts named “sarabba__instant”. The evaluation is conducted using data from questionnaires and monthly sales change data. The expectation is that the public will be able to acquire valuable information by reading or simply viewing Instagram social media as a promotional media.